Migration creation, diversion, and retention: new deal grants and migration ; 1935 - 1940 - Todd A. Sorensen; Price Fishback; Samuel K. Allen; Shawn Kantor (Institute for the Study of Labor (IZA), 2007)
During the 1930s the federal government embarked upon an ambitious series of grant programs designed to counteract the Great Depression. Public works and relief programs combated unemployment by hiring workers and building social overhead capital while the Agricultural Adjustment Administration (AAA) sought to raise farm incomes by paying farmers not to produce. The amounts distributed varied widely across the country and potentially contributed to population shifts. We examine the extent to which New Deal spending affected domestic migration patterns in the second half of the 1930s. We estimate an aggregate discrete choice model, in which household heads choose among 466 economic subregions. The structural model allows us to decompose the effects of program spending on migration into three categories: the effect of spending on keeping households in their origin (retention), the effect of pulling non-migrants out of their origin (creation), and the effect of causing migrants to substitute away from an alternative destination (diversion). An additional dollar of public works and relief spending increased net migration into an area primarily by retaining the existing population and creating new migration into the county. Only a small share of the increase in net migration rate was caused by diversion of people who had already chosen to migrate. AAA spending contributed to net out migration, primarily by creating new out migrants and repelling potential in migrants. A counterfactual analysis that examines what would have happened had there been no New Deal spending during the 1930s suggests that the uneven distribution of New Deal public works and relief spending explains about twelve percent of the internal migration flows in the United States between 1935 and 1940. The uneven distribution of AAA spending accounted for about one percent.
Keywords: 330; Migration; new deal; discrete choice; Wirtschaftskrise; Öffentlicher Transfer; Wirtschaftsförderung; Binnenwanderung; New Deal; USA